Novel Mannitol-Based Small Molecules for Inhibiting Aggregation of α-Synuclein Amyloids in Parkinson's Disease - Paul, Ashim; Zhang, Bo-Dou; Mohapatra, Satabdee; Li, Gao; Li, Yan-Mei; Gazit, Ehud; Segal, Daniel (Frontiers in Molecular Biosciences, 2019)
The aggregation of the amyloidogenic protein α-synuclein (α-Syn) into toxic oligomers and mature fibrils is the major pathological hallmark of Parkinson's disease (PD). Small molecules that inhibit α-Syn aggregation thus may be useful therapeutics for PD. Mannitol and naphthoquinone-tryptophan (NQTrp) have been shown in the past to inhibit α-Syn aggregation by different mechanisms. Herein, we tested whether the conjugation of Mannitol and NQTrp may result in enhance efficacy toward α-Syn. The molecules were conjugated either by a click linker or via a PEG linker. The effect of the conjugate molecules on α-Syn aggregation in vitro was monitored using Thioflavin T fluorescence assay, circular dichroism, transmission electron microscopy, and Congo red birefringence assay. One of the conjugate molecules was found to be more effective than the two parent molecules and as effective as a mixture of the two. The conjugate molecules attenuated the disruptive effect of α-Syn on artificial membrane of Large Unilamellar Vesicles as monitored by dye leakage assay. The conjugates were found to be have low cytotoxicity and reduced toxicity of α-Syn toward SH-SY5Y neuroblastoma cells. These novel designed entities can be attractive scaffold for the development of therapeutic agents for PD.